Accelerated carbonation of hardened cement pastes: Influence of porosity. (20th November 2019) - Wang, Jinbang; Xu, Hongxin; Xu, Dongyu; Du, Peng; Zhou, Zonghui; Yuan, Lianwang; Cheng, Xin
Highlights: Thestrength of samples carbonation curing for 4h are higher than water curing for 7 d. The pores larger than 200 nm played a leading role in carbon dioxide diffusion. The major reactants in the carbonation reaction were C2 S, C3 S, and a few (Ca(OH)2 ). The carbonation curing mechanism of hardened cement pastes are discussed. Abstract: Recently, with the development of accelerating mineral carbonation technology, the preparation of building materials by using carbonation curing cement-based materials has attracted wide attention. The diffusion and transfer mechanism of carbon dioxide in porous cementitious materials was the key point that restricts the improvement of materials carbonation rate. In order to obtain comprehensive information that affects accelerating carbonation rate of porous cement-based materials, this paper talks about the influences of paste porosity controlled by water to cement ratio (w/c) on carbonation and the paste micro-structures evolution. Also, mineral compositions before and after carbonation curing were evaluated. Results show that the carbonation rate, carbonation depth and compressive strength are improved after carbonation, while total porosity of complete carbonation zone decreases with the growth of paste porosity. The pores with diameter larger than 200 nm played a leading role in carbon dioxide diffusion, which were reduced by 84.25% of the total volume after carbonation curing. The carbonization reaction mainly occurred in the first six hours in carbonation curing, while the subsequent carbonation curing were unprofitable to the carbonation effect due to the generation of calcium carbonate prevents the diffusion of CO2, making the subsequent carbonation become difficult. XRD results revealed that during carbonation curing the major reactants were C2 S, C3 S and some hydration products of Ca(OH)2 after 1 d hydration.